Digital Authoritarianism and the Crisis of Press Freedom in the Philippines - Fernández, Lucas Hallberg; Scoccola, Lucinao; Arrachea, Feresin Gabriela (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This study explores the emergence and consolidation of digital authoritarianism in the Philippines, particularly under the administrations of Rodrigo Duterte and Ferdinand Marcos Jr. Drawing on discourse analysis, secondary interviews, and institutional reports, the article investigates how state actors employ algorithmic surveillance, legal harassment, and disinformation campaigns to suppress critical media. By analyzing key cases such as the legal persecution of journalist Maria Ressa and Rappler, the study reveals the mechanisms through which press freedom is undermined in digital spaces. The research adopts a descriptive qualitative approach, engaging with policy documents, human rights reports, and digital media analytics to assess how digital tools are repurposed for authoritarian consolidation. Findings indicate that the government’s use of cybersecurity laws, troll networks, and selective enforcement contributes to a chilling effect on independent journalism. This phenomenon signals a shift from traditional censorship to hybrid, algorithm-driven repression. The study contributes to the broader discourse on media freedom, digital rights, and democratic backsliding in Southeast Asia. It underscores the need for regional policy coordination, digital literacy, and institutional resilience to counter authoritarian innovation in cyberspace. Future research may expand this inquiry by examining comparative cases in neighboring ASEAN states.